Social Responsibility in Kurdistan Oil and Gas Sector - Dr. Umed Sabah Othman; Dr. Tahsen Hamad Smailm; Hemdad Faisal AHmad (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The concept of corporate social responsibility CSR is receiving spectacular attention in recent years both from the business practitioners as well as academicians in different parts of the world, and there is no exception from the developing countries to this phenomenon. This paper will discuss the reality of CSR performed by the oil and gas companies in Kurdistan. The perspective approach to discuss the meaning and advantages of CSR, and data analysis approach to explain the reality of CSR in Kurdistan have been adopted as a research method.